Computer assisted audiometric evaluation system - Weiss, Martin (Division of Biomedical Engineering, 2017)
A computer-based audiometric evaluation system has been developed. The system makes use of an IBM PC/XT/AT compatible personal computer to perform pure tone and speech tests and · comprises a plug-in card and custom software. The card contains pure tone and masking noise generators, together with amplifiers for a. set of headphones .and bone conduction transducer, patient and audiologist microphone amplifiers and a hand-held infra-red remote-control unit. A voice-operated gain-adjusting device on the audiologist's microphone eliminates the need for a sound pressure level meter during speech tests. The software-based user-interface makes use.of overlaid pop-up menus, context sensitive assistance.and a text editor on a graphics screen. Pure tone and speech data are acquired and displayed on a dynamic audiogram and speech discrimination gram respectively. This data may be stored and later retrieved from a patient data base. Further audiometric tests may be incorporated at a later stage.